DAMPAK PERCERAIAN TERHADAP PSIKOLOGIS, EMOSIONAL DAN MENTAL ANAK DALAM PERSPEKTIF HUKUM ISLAM - Muhammad Syarif (SYARIAH: Journal of Islamic Law, 2022)
Every human being certainly has the hope of building a family which is the goal of marriage law, namely building a good familysakinah, mawaddah wa rahmah. However, there are various factors that cause the breakdown and destruction of a household so that they choose to divorce. The consequences of the divorce will damage the relationship between husband and wife and have an impact on the psychological, emotional and mental well-being of the child.Collecting data with a literature study approach (library research), which is done by searching for data or research information through reading scientific journals, reference books and publication materials available in various sources. The results of this study indicate that husband and wife sometimes have to face problems in their household life, the emergence of problems in the household can be caused by many things including economic factors, lack of sense of responsibility, differences in outlook on life which can result in a household crisis. A woman who is about to become a widow doesn't think about what other people think of her because according to her this is her life and she is the one who is going through it all, it's just that there is guilt for her child when she has to get a divorce. Of course there is an impact of divorce that will arise on the psychological development of their children, trying so that their children do not lose the love of a father.